Processing Wastewaters from Spanish-Style cv. Chalkidiki Green Olives: A Potential Source of Enterococcus casseliflavus and Hydroxytyrosol - Papadaki, Eugenia; Botsaris, George; Athanasiadi, Athanasiadi; Mantzouridou, Fani Th. (My University, 2020)
The purpose of this study was to examine the isolation of indigenous lactic acid bacteria (LAB) with functional properties from Spanish-style cv. Chalkidiki green olive processing wastewaters (GOW). Predominant indigenous LAB could serve as bioaugmentation agents/starter culture for table olives production and protected designation of origin specification. Spontaneous fermentation of fresh GOW over different temperatures (15 °C to 50 °C) and pH values (3.5 to 11.5) for 30 d enabled the isolation/molecular identification of the lactic acid bacterium Enterococcus casseliflavus and the plant-associated bacterium Bacillus amyloliquefaciens subsp. plantarum. E. casseliflavus was found to reduce chemical oxygen demand by 72%. Its resistance to extreme pH values, salinity, and temperature was successfully modeled and the minimum inhibitory concentration of oleuropein against the bacterial growth was determined (0.9 g/L). Furthermore, hydroxytyrosol content was doubled (up to 553 mg/L) after GOW spontaneous fermentation under acidic conditions at 15 °C to 30 °C for 120 d, creating an additional source of input. These results highlight the significance and potential of E. casseliflavus in Spanish-style cv. Chalkidiki green olive processing.
Keywords: Table olive wastewaters; Lactic acid bacteria; Enterococcus casseliflavus; Bacillus amyloliquefaciens subsp. plantarum; 16S rRNA gene sequencing; Bioaugmentation; Oleuropein hydrolysis; Hydroxytyrosol